Phytosociological contrast of ferns and lycophytes from forest fragments with different surroundings matrices in southern Brazil - Silva,V. L. (2019)
Abstract Forest edges typically exhibit higher luminosity and lower humidity than the forest interior, resulting in an abiotic gradient. However, the degree of abiotic difference can be affected from the type of the matrix, influencing the selection of species. We compared the floristic and phytosociological structure of understory communities of ferns and lycophytes of the edge and interior of three forest sites influenced by different types of surrounding matrices (natural field, Pinus plantation, and cultivation of crops). In the region of Araucaria Forest, in Rio Grande do Sul, Brazil, twelve 10 × 10 m plots were selected at the edge and interior of each site, totaling 72 plots and to evaluate the phytosociological contrast, using as a parameter coverage and species richness per plot to evaluate this contrast. We recorded a total of 38 species in the studied areas, distributed in 15 families. The results show that the edge effect acts at different intensities in the analyzed sites. In the site with unnatural matrix, the composition was more homogeneous both in the edges and in the interiors and presented lower richness, showing a more pronounced and deep impact. Already in the site with natural matrix surroundings, although the border also presents low richness, the interior was about 3x richer. Based on our results, we concluded that fern conservation efforts should focus on fragments of Araucaria Forest inserted in the natural field, because the conversion of natural field into Pinus planting and cultivation of crops decreases ferns species both in the edges and forest interiors of the studied fragments, besides altering the phytosociological structure leading the communities to simplification.